A Motivation Analysis of Video Game Microstreamers: "Finding My People and Myself" on YouTube and Twitch. Issue 2 (15th March 2022) - Young, Andrew; Wiedenfeld, Grant
ABSTRACT: Microstreamers broadcast their video game play and commentary to small audiences on YouTube and Twitch. To draw a holistic picture of their motivations, this study conducted semi-structured interviews employing two complementary frameworks. A Uses and Gratifications approach showed that social integrative needs predominate – even personal integrative and affective need satisfaction depend on audience. In parallel, a Self-Determination Theory approach demonstrated satisfaction of three fundamental needs: the autonomy of an artist–entrepreneur; the relatedness of a community leader; and skill competence displayed to an audience. Microstreamers are driven to "find their people" online, where, through performance, they "find themselves" anew.